Globalization, Nation-State, and Local Identity A Study of an Affair between the Movement of Religious Formalization and the Discourse of Local Identity in Kalimantan Selatan - Irfan Noor (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
The formalization movement of Islamic sharia which is currently prevalent in Indonesia has succeeded in taking advantage of the development of the discourse of strengthening local identity in the Regional Autonomy era. One of the successes of this movement is the issuance of various local regulations with nuances of Islamic sharia in various regions in Indonesia. One area that currently shows such a trend is South Kalimantan. In this area, the starting point of the development of the discourse of affirming local identity is the negative impact of global culture that synergizes with the totalitarianism of the construct of the nation state. Therefore, when the distinctive character developed by the Islamism movement is a counter-ideology towards various modernism and secularism, this movement is able to intertwine with local identity affirmation discourse which also develops an resistance to the nation-state construct tend to be totalitarianism in the style of the New Order which is also a product of modernism. As a result, various local regulations on Islamic sharia are discriminatory, sectarian, corruptive, and intolerant of the diversity of national culture.